Verification of InaCAWO Model Surface Ocean Currents Based on HF Radar Data in the Labuan Bajo Waters - Panji Kuswanaji; Aries Kristianto (Departement of Physics Faculty of Mathematics and Natural Sciences, and Institute of Research and Community Services Udayana University, Kampus Bukit Jimbaran Badung Bali, 2026)
Labuan Bajo waters are a strategic maritime region with intensive tourism and marine transportation activities, making surface current information essential for maritime safety. This study aims to verify surface ocean current outputs from the InaCAWO model using HF Radar observations in Labuan Bajo as reference data. The study used surface current zonal (u) and meridional (v) components from InaCAWO and HF Radar for the period 1 December 2024 to 31 May 2025. Spatial resolution differences between the two datasets were adjusted using Natural Neighbor Interpolation, by interpolating HF Radar data onto the InaCAWO model grid. Model verification was conducted using statistical indicators, including Bias, Mean Absolute Error (MAE), Root Mean Square Error (RMSE), and Willmott Index, and supported by analyses of mean surface current, time series, scatterplots, and monthly spatial distributions of current components. The results show that InaCAWO is able to represent the general pattern of surface currents in Labuan Bajo waters, but tends to produce lower current magnitudes than HF Radar observations. The time series comparison shows a bias of -0.34 knot, an RMSE of 0.41 knot, and a correlation of 0.25, indicating a weak temporal relationship and an underestimation tendency. Verification of u and v components shows spatially and temporally varying errors, with greater uncertainty in the meridional component. Therefore, InaCAWO can serve as an initial representation of surface current conditions, but further evaluation is needed to improve its accuracy in capturing local current dynamics.